'Curb sitting': An evidence-based policing practice or an officer safety myth?. (2nd January 2023) - Blake, David; Suss, Joel; Wolfe, Duane; Arsal, Güler
ABSTRACT: Law enforcement officers across the country are trained in various tactics and techniques intended to increase the overall safety within a police-citizen contact. One common, albeit controversial tactic is referred to as "curb sitting". The curb-sitting tactic is generally associated with officers requiring criminal suspects to sit on a curb with their legs outstretched in front of them. The tactic is believed to provide officers additional reaction time to defend themselves from an attack but is also considered unnecessarily demeaning. The efficacy of the curb-sitting tactic has not previously been determined. The current study is the first to evaluate three common variations of the curb-sitting tactic to determine which, if any seated position allowed officers more time to respond to an attack when compared to a subject standing five feet away. Our results show that a seated subject with their legs extended is associated with a significant increase in time to cross five feet when compared to a standing subject. Based on these results, the curb-sitting tactic appears to be an evidence-based method of increasing an officer's time to respond to an attack. Implications for law enforcement training and tactics, as well as recommendations for future research are discussed.